Evidence use in the UK’s COVID-19 free school meals policy: a thematic content analysis - Jennie C. Parnham; Sarah McKevitt; Eszter P. Vamos; Anthony A. Laverty (Policy Design and Practice, 2023)
AbstractFree school meals (FSM) are a well-recognized intervention for tackling food insecurity among school children. National school closures during the COVID-19 pandemic meant that there was a need to rapidly adapt the delivery of FSM. A range of food-assistance policies were implemented, but it is not clear if they were evidence-based. This study aimed to determine the transparency of evidence use and identify other competing influences in the UK’s FSM policy decisions. Thematic content analysis was used to review 50 publicly available policy documents and debate transcripts on FSM policy published between March 2020 and 2021. This period covered the first national school closures (March 2020–July 2020), school holidays, and the second national school closures (January 2021–March 2021). The Evidence Transparency Framework (ETF) was used to assess the transparency of evidence use in policy documents. We found that overall transparency of evidence use was poor but was better for the Holiday Activities and Food (HAF) program. The Government showed preference for replacing FSM with food parcels, rather than more agentic modes of food assistance, such as cash-vouchers. This preference appeared to be closely aligned with ideological views on the welfare state. With an absence of evidence, value-based reasoning took precedent and was polarized by social media. This article highlights the need for a formal review into FSM, one which includes a comparison of low and high agentic food assistance policies. Such a review would address the evidence gap, improve food assistance policy, and aid policymakers in future periods of uncertainty.